因式分解3(x+1)-(x+1)的平方把下列各式因式分解3(x+1)-(x+1)平方3(x-y)-2(x-y)的平方5m(a+b)-a-b

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 00:15:33
因式分解3(x+1)-(x+1)的平方把下列各式因式分解3(x+1)-(x+1)平方3(x-y)-2(x-y)的平方5m(a+b)-a-b因式分解3(x+1)-(x+1)的平方把下列各式因式分解3(x

因式分解3(x+1)-(x+1)的平方把下列各式因式分解3(x+1)-(x+1)平方3(x-y)-2(x-y)的平方5m(a+b)-a-b
因式分解3(x+1)-(x+1)的平方
把下列各式因式分解
3(x+1)-(x+1)平方
3(x-y)-2(x-y)的平方
5m(a+b)-a-b

因式分解3(x+1)-(x+1)的平方把下列各式因式分解3(x+1)-(x+1)平方3(x-y)-2(x-y)的平方5m(a+b)-a-b

3(x+1)-(x+1)²
=(x+1)[3-(x+1)]
=(x+1)(2-x)
3(x-y)-2(x-y)²
=(x-y)[3-2(x-y)]
=(x-y)(2y-2x+3)
5m(a+b)-a-b
=5m(a+b)-(a+b)
=(5m-1)(a+b)

3(x+1)-(x+1)²
=(x+1)(2-x)
3(x-y)-2(x-y)²
=(x-y)(3-2x+2y)
5m(a+b)-a-b
=5m(a+b)-(a+b)
=(5m-1)(a+b)